Study of staffing conditions to identify the adaptability of Russian higher education institutions to develop international cooperation using digital learning technologies - M. A. Tanina; V. V. Bondarenko; V. A. Yudina; D. P. Penzina (Вестник университета)
In current conditions of economic and political tension, it is extremely urgent to conduct a study of the adaptability of the higher education system of the Russian Federation to the development of international cooperation with the use of digital educational technologies. At the same time, one of the key resources used in the implementation of international cooperation mechanisms in the higher education system is the staffing of Russian universities. The study is analysed the staffing effectiveness of the Russian universities for compliance with the current requirements of the digital and distance learning technologies market, and readiness for the use of mechanisms for the development of international cooperation in the context of global digitalisation of the educational space according to statistical data was carried out. The dynamics of the digital literacy index of scientific and pedagogical staff in the Russian universities is analysed. The correlation and regression analysis of the relationship between the number of foreign students studying in Russia and the indicators of research performance, tenure and the digital literacy index of scientific and pedagogical staff in the Russian Federation revealed strong direct correlations. It has been concluded that the increase in the efficiency of staffing and the growth of digital literacy of scientific and pedagogical staff of Russian universities will have a positive impact on the competitiveness and adaptability of the higher education system of the Russian Federation in the international educational market.